The Jewish origins of Christianity - Fischer, Raymond Robert; Olim Publications; DVD Foundry (Tiberias, Israel : Olim Publications : DVD Foundry, 2004)
This 16-unit course demonstrates the Jewish roots of Christianity from both a biblical and a historical perspective. Consists of slide presentations and audio narration by the instructor, Dr. Raymond Robert (Bob) Fischer.
"DVD version of the regular 4 credit hour course 'Christian Origins' (NT5215) offered in residence by Faith Seminary in Tacoma, Washington. Undergraduate or graduate level college credit for its successful completion can be arranged with the Seminary"--Container.
Accompanying CD-ROM includes final examination and suggested reading.
DVD; Dolby Digital.
Keywords: Dead Sea scrolls -- Criticism, interpretation, etc; Christianity and other religions -- Judaism; Judaism -- Relations -- Christianity; Judaism (Christian theology)